Viral Content Impact on Local Brand Growth - Adam Harahap, Nasywa Fatihah; Osly Usman, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
Abstract This research analyzes the influence of viral marketing, content type, and content quality on the development of local brands on the TikTok platform, with user retention as an intervening variable. Living in the digital era, TikTok has become one of the most effective platforms to establish brand awareness by creating viral marketing that can attract the users' attention widely. Aside from that, diverse forms of content and quality of the content published will also exert a significant effect on developing positive perceptions toward local brands. The quantitative approach of this study collected data from questionnaires circulated to users on TikTok who have engaged in any form of activity with a local brand on the platform. The path analysis model test shall be among the independent variables: viral marketing, content type, and content quality; intervening variable: user retention; and dependent variable, which is local brand development. From the research findings, it follows that viral marketing, content type, and content quality are significantly affecting user retention, affecting local brand development. Retention of users has been cited as the most influential aspect in solidifying the relationship between the efficiency of marketing strategies on TikTok and the performance of local brands. The contribution of this study will be towards the strategies of digital marketing, especially on how to use social media as an effective tool in raising brand awareness and building consumer loyalty. Keyword: Viral Marketing, Content Type, Content Quality, User Retention, Development of Local Brand.